2021
DOI: 10.1111/jpi.12745
|View full text |Cite
|
Sign up to set email alerts
|

A classification approach to estimating human circadian phase under circadian alignment from actigraphy and photometry data

Abstract: The time of dim light melatonin onset (DLMO) is the gold standard for circadian phase assessment in humans, but collection of samples for DLMO is time and resourceintensive. Numerous studies have attempted to estimate circadian phase from actigraphy data, but most of these studies have involved individuals on controlled and stable sleep-wake schedules, with mean errors reported between 0.5 and 1 hour. We found that such algorithms are less successful in estimating DLMO in a population of college students with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 56 publications
(96 reference statements)
0
13
0
Order By: Relevance
“…This model has been validated against multiple carefully controlled laboratory studies ( 35 , 36 ), and light level (in lux) is the only input in the original design of the model. However, recent advances in the field have shown that incorporating activity is necessary to predict the circadian phase in the field setting ( 5 , 12 , 37 ). In particular, activity is correlated with light, and it has been shown that replacing light by activity levels measured from wearable devices coupled with the mathematical model can predict circadian phase with an error within 1 h for people living in regular conditions ( 5 , 12 ), Initial conditions were generated from a limit-cycle [as in Huang et al ( 5 )]: the start point was determined to be 35 days prior to the social distancing date, and the model was simulated until 35 days after social distancing.…”
Section: Methodsmentioning
confidence: 99%
“…This model has been validated against multiple carefully controlled laboratory studies ( 35 , 36 ), and light level (in lux) is the only input in the original design of the model. However, recent advances in the field have shown that incorporating activity is necessary to predict the circadian phase in the field setting ( 5 , 12 , 37 ). In particular, activity is correlated with light, and it has been shown that replacing light by activity levels measured from wearable devices coupled with the mathematical model can predict circadian phase with an error within 1 h for people living in regular conditions ( 5 , 12 ), Initial conditions were generated from a limit-cycle [as in Huang et al ( 5 )]: the start point was determined to be 35 days prior to the social distancing date, and the model was simulated until 35 days after social distancing.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, recent circadian modelling research has indicated that lighting conditions bear strong predictive influence over circadian angle of entrainment and preferred sleep timing (Papatsimpa et al, 2021;Phillips et al, 2019). Allowing BMM circadian phase parameters to be informed from actigraphy and photometry data passively (see Brown et al, 2021) would reduce model complexity and improve predictive accuracy.…”
Section: Model Individualization and Real-time Predictionmentioning
confidence: 99%
“…Rhythmic fluctuations driven by the core clock could be illustrated as a sinusoidal curve with a period of about 24 hours [8], and hence the circadian rhythms are typically described using three key parameters (Supplementary Figure 1): period (the length of one cycle), phase (the timing of a reference point in the cycle relative to a fixed event), and amplitude (the difference between crest and trough values of the cycle) [9]. While methods for measuring period [10,11] and phase [12][13][14][15][16][17] are well-established and accurate in both laboratory and field studies, assessing circadian amplitude remains challenging.…”
Section: Introductionmentioning
confidence: 99%